Identification and Characterization of a Thermotolerant TILLING Allele of Heat Shock Binding Protein 1 in Tomato - Marko, Dominik (Genes (Basel), 2019)
The identification of heat stress (HS)-resilient germplasm is important to ensure food security under less favorable environmental conditions. For that, germplasm with an altered activity of factors regulating the HS response is an important genetic tool for crop improvement. Heat shock binding protein (HSBP) is one of the main negative regulators of HS response, acting as a repressor of the activity of HS transcription factors. We identified a TILLING allele of Solanum lycopersicum (tomato) HSBP1. We examined the effects of the mutation on the functionality of the protein in tomato protoplasts, and compared the thermotolerance capacity of lines carrying the wild-type and mutant alleles of HSBP1. The methionine-to-isoleucine mutation in the central heptad repeats of HSBP1 leads to a partial loss of protein function, thereby reducing the inhibitory effect on Hsf activity. Mutant seedlings show enhanced basal thermotolerance, while mature plants exhibit increased resilience in repeated HS treatments, as shown by several physiological parameters. Importantly, plants that are homozygous for the wild-type or mutant HSBP1 alleles showed no significant differences under non-stressed conditions. Altogether, these results indicate that the identified mutant HSBP1 allele can be used as a genetic tool in breeding, aiming to improve the thermotolerance of tomato varieties.